RANCANG BANGUN SYRINGE PUMP - Falista M, Hafidz (Elektrika, 2017)
A syringe pump is a tool for inserting high-dose drug fluids given to patients. The accuracy and accuracy of the amount of fluid given to this device are quite high. The need for this tool in hospitals is very large, but in terms of the economy, the price of the equipment is still very expensive so it is not affordable for small hospitals. The purpose of making a syringe pump is to be able to meet the needs of the syringe pump in small hospitals so that it can save on budget expenses. Therefore a syringe pump is designed, designed using the Arduino Nano as a control system, display flow speed with 16x2 LCD, stepper motor as a syringe booster according to the regulated flow speed, and buzzer as an alarm when a blockage occurs and the syringe placement is incorrect. Flowrate parameters at a speed of 10 ml / hour, 20 ml / hour, 30 ml / hour, 40 ml / hour and 50 ml / hour.Keywords: Syringe Pump, flowrate, stepper motor, Arduino Nano